Red Dragon (Hylocereus polarizes) Fruit Peel Herbal Tea with The Addition of Cinnamon, Ginger, and Orange Zest - Abdul Halik; Fatmawati; Jannati Tangngisalu (Institut Pertanian Bogor, 2025)
The peel of dragon fruit is a waste. The meat of dragon fruit is the most frequently consumed; the peel is rarely used and is only wasted. The natural antioxidant lycopene may be found in the skin of dragon fruit. Dragon fruit skin can be processed to make herbal tea. This study aims to ascertain the yield, moisture content, and organoleptic testing to produce dragon fruit peel tea and the effects of adding cinnamon, ginger, and lemon zest. The research treatments included lemon zest at 40%, ginger at 14%, and cinnamon at 6% concentrations. Three treatment levels and three replications were employed in the fully randomized design (CRD) for data analysis. According to the study's findings, the best way to treat a dragon fruit peel herbal tea bag that contains 6% cinnamon powder was to know how adding cinnamon, ginger, and lemon zest to the process of making dragon fruit peel tea affects the yield, moisture content, and organoleptic test. According to the respondents' liking, the taste test scored 3.91%, scent 3.88%, and color 4.45% (loved) (liked). Based on SNI 3836.2013 about tea quality criteria, which stipulates that the maximum moisture content included in tea powder is 8%, a yield of 8.64%, and a moisture content of 0.48% satisfy the tea quality requirements. Keywords: dragon fruit peel, cinnamon, ginger, lemon zest, red dragon fruit peel tea